Perancangan Sistem Informasi Pelayanan Masyarakat Berbasis Web Di Kantor Desa Medan Mas Kecamatan Batu Ampar Kabupaten Kubu Raya - Wahsyahlan, Ahlan; Maulana, Adha; badra, Aditya Pratama (Al-Mantiq, 2025)
The rapid development of information technology has significantly transformed various sectors, including public services at the village level. Medan Mas Village, located in Batu Ampar Subdistrict, Kubu Raya Regency, still operates its administrative services manually, particularly in document submission and information dissemination. This condition leads to several issues such as delayed communication, long queues at the village office, and high risk of data loss due to conventional file management systems. This research aims to design a web-based public service information system as a solution to the problems faced by the Medan Mas Village Office. The methodology used in this study includes observation, interviews, system requirements analysis, and system design using modeling tools such as use case diagrams, activity diagrams, and database design. The proposed system includes main features such as village news updates, online letter submission, submission status tracking, and employee data management. The results of the design show that the system can provide convenience for residents to access administrative services without the need to visit the village office physically. Additionally, it helps village officials manage data more effectively, efficiently, and in a well-structured manner. Therefore, the system is expected to be an initial step toward digital transformation of village-level public services that are modern, transparent, and accessible.